P182. Patterns of gait-related electrophysiological activity in the human subthalamic nucleus of patients with Parkinson's disease. Issue 8 (August 2015) - Hell, F.L.; Boetzel, K.; Plate, A.; Hathway, P.; Mehrkens, J.H.; Kammermeier, S.; Ilmberger, J.
<x xml:space="preserve">Abstract</x> Problems during gait constitute a severe disability for patients with Parkinson's disease (PD) and lead to significant limitations during their daily life, especially in later stages of the disease. The nuclei of the basal ganglia are crucial for important aspects of motor processes and are used as target areas for deep brain stimulation therapy of the motor symptoms associated with PD. Investigations of the (patho)-physiology of these structures during gait should therefore contribute to our understanding of the neuronal processes involved during normal movement and clarify if symptom-specific pathological neuronal activity can be characterized. For this purpose, we investigated the electric local field potentials of the subthalamic nucleus of 12 patients with PD recorded from deep brain stimulation electrodes during walking and during rest. Simultaneously, the movement of the patients was recorded with inertial sensor units and subsequently analyzed in parallel to the electrophysiological activity. In this way, gait patterns like normal walking or akinetic freezing epochs can be reconstructed and their specific neuronal activity can be described with the analysis of the electrophysiological recordings. Attenuation of oscillations in the beta frequency band (12–35 Hz) can be observed in patients without freezing epochs during normal walking as compared to rest. In contrast, patients with freezing epochs show an increase in lower beta frequency (12–22 Hz) amplitude during walking as compared to rest as well as freezing epochs themselves show increased lower beta frequency as compared to normal walking and rest. Both, patients with nearly regular gait and patients with akinetic epochs did show an increase in the gamma frequency band (35–90 Hz) during movement. Our results show that an increase of oscillations in the lower beta band is highly correlated with severe freezing epochs and might possibly play a causal role for akinesia in PD. Such a symptom-specific and characteristic electrophysiological fingerprint could be used as a kind of marker of pathological neuronal activity for the adjustment of the deep brain stimulation therapy in a closed-loop fashion.